Fenomena Thrifting dalam Pandangan Jean Baudrillard: Studi Kasus Pasar Cimol Gedebage - Rizqi Faisal Muzaqi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the phenomenon of thrifting in the view of Jean Baudrillard. This research uses a qualitative approach by applying field studies through observation. The formal object of this research is the theory of simulacra in the view of Jean Baudrillard. The material object of this research is thrifting phenomenon. As for the observations carried out on economic activity in Pasar Cimol Gedebage Bandung as the context of this research. The results and discussion of this study indicate that consumption behavior for Jean Baudrillard is conceptualized as the process of actively buying an item, with an effort to create and maintain a sense of identity through the goods it buys. This study concludes that there is a thrifting phenomenon at Pasar Cimol Gedebage Bandung as a form of consumptive behavior that emphasizes this behavior as if it has a feeling that it has gone with the times for the purpose of recognition as an upper class society.